Efektivitas Media Sosial Sebagai Sarana Promosi Hotel Sibayak Internasional Berastagi - Silalahi, Rikki Sembari; Emrizal, Emrizal; Hanafi, M. Hirsan (Politeknik Pariwisata Medan, 2023)
This study aims to determine the effectiveness of social media as a promotional tool for Hotel Sibayak Internasional Berastagi. This study uses a qualitative method with a descriptive approach to the data obtained in the study using primary data by conducting field observations, interviewing the Sales & Marketing team, and conducting documentation during the research. The results obtained from this study indicate the use of social media as a means of effective promotion. carried out by the Sales & Marketing team by providing digital product information in the form of product photos in the form of posters and videos These are used to reach potential customers.